2022
DOI: 10.3390/jcm11041139
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in the Prophylaxis of SARS-CoV-2 Infection in Healthcare Workers (MeCOVID): A Randomised Clinical Trial

Abstract: We evaluated in this randomised, double-blind clinical trial the efficacy of melatonin as a prophylactic treatment for prevention of SARS-CoV-2 infection among healthcare workers at high risk of SARS-CoV-2 exposure. Healthcare workers fulfilling inclusion criteria were recruited in five hospitals in Spain and were randomised 1:1 to receive melatonin 2 mg administered orally for 12 weeks or placebo. The main outcome was the number of SARS-CoV-2 infections. A total of 344 volunteers were screened, and 314 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…36 There was no statistically significant difference in the number of SARS-CoV-2 infections between the melatonin and placebo arms. 36 It is worth noting that the melatonin group showed a higher incidence of subjectively reported adverse events, including somnolence, in comparison to the placebo group. However, no severe adverse events related to treatment were reported during the study.…”
Section: Animal Studies Evaluating the Antiviral Effect Of Melatoninmentioning
confidence: 85%
See 1 more Smart Citation
“…36 There was no statistically significant difference in the number of SARS-CoV-2 infections between the melatonin and placebo arms. 36 It is worth noting that the melatonin group showed a higher incidence of subjectively reported adverse events, including somnolence, in comparison to the placebo group. However, no severe adverse events related to treatment were reported during the study.…”
Section: Animal Studies Evaluating the Antiviral Effect Of Melatoninmentioning
confidence: 85%
“…However, no severe adverse events related to treatment were reported during the study. 36 This trial is one of the few published investigations into melatonin's potential as a prophylactic treatment for SARS-CoV-2 infection. In this trial it is important to consider the limitations outlined in the study, as they may have led to the non-significant results.…”
Section: Animal Studies Evaluating the Antiviral Effect Of Melatoninmentioning
confidence: 99%
“…They concluded that the use of melatonin supplements could help reduce thrombosis, sepsis, and mortality in COVID19 patients [71]. In another study by García‐García et al [72] in which they evaluated melatonin's effect as a preventative measure against SARS‐CoV‐2 infection among healthcare workers at high risk of exposure to the virus in a randomized, double‐blind clinical trial. A total of 308 received the study treatment (148 placebo; 160 melatonin).…”
Section: Clinical and Preclinical Evidence That Use Melatonin As A Tr...mentioning
confidence: 99%
“…Further favorable effects of melatonin receptors in the COVID-19 context are their synchronizing effect on biological rhythms and their sleep-initiating properties that might be beneficial for intensive care patients suffering from disrupted sleep patterns or sleep deprivation, which favors the production of inflammatory cytokines and predisposition to lung inflammation [ 30 ]. First results from clinical trials on the effect of melatonin in critically ill patients with SARS-CoV-2 infection report a significantly improved clinical status when given as an adjunctive agent in combination with basic treatments in some studies but not in others without any apparent adverse events (Ref) [ [31] , [32] , [33] , [34] ].…”
Section: Introductionmentioning
confidence: 99%